ON GENERALIZED STATISTICAL CONVERGENCE OF ORDER ˜? VIA IDEAL WITH RESPECT TO MODULUS FUNCTION - Kişi, Ömer; Akbıyık, Rumeysa; Gürdal, Mehmet; Kişi, Ömer; Kişi, Ömer (Gakko Tosho Co. Ltd., 2024)
In this paper, we define new notions of (f, I)-statistical convergence for triple sequences of order ? and strong (f, I)-Cesàro summability for triple sequences of order ?. Furthermore, we examine the relationships among the spaces. Additionally, we present the concepts of (f, I)-lacunary statistical convergence of order ? and strong (f, I)-lacunary summability of order ? for triple sequences, providing inclusion relations among these new concepts. © 2025 Elsevier B.V., All rights reserved.
Keywords: Cesàro Summability Method; Statistical Convergence; Triple Sequences